26.1k views
5 votes
Simplify the following expression. Leave your answer in the form a^b.3^19/3^13= ___

Simplify the following expression. Leave your answer in the form a^b.3^19/3^13= ___-example-1

1 Answer

3 votes

Given the expression:


(3^(19))/(3^(13))

To simplify the expression, we will use the following rule of the exponents:


(a^m)/(a^n)=a^(m-n)

The answer will be:


\begin{gathered} (3^(19))/(3^(13))=3^(19-13)^{} \\ \\ =3^6 \end{gathered}

you will write the answer as 3^6

User Dustin Cochran
by
5.6k points